Crystal-Liquid Segregation in Silicocarbonatite Magma Leads to the Formation of Calcite Carbonatite. (21st June 2022) - Moore, K R; Brady, A E; Costanzo, A
Abstract: A suite of silicocarbonatite and lamprophyre rocks from SW Ireland, with mantle affinity and primitive composition, are used as a proxy for parental carbonated silicate magmas to model early magmatic evolution. Reconstruction of volatile ratios is validated using global occurrences. At 1200°C, the point at which melts transition from ionic liquids with exceptionally low viscosity (0.06 PaS) to covalently polymerised liquid (viscosity up to 1.3 PaS) is 33 mol% SiO2 . Incremental and significant increase in magma density accompanies magma ponding, due to dehydration of magmas from model molar CO2 /(CO2 + H2 O) of 0.60 in plutonic settings to 0.75 for initial subvolcanic magmas. Magma-crystal density differences dictate that repeated influxes of magmas into an inflating magma chamber sustain a mechanical boundary layer between dense (silicate and oxide) mineral layers and a calcite ± phlogopite flotation assemblage. The range of critical CO2 concentration at which calcite floats (10–13 wt% CO2 ) may be extended by the presence of additional volatiles and fluid bubbles. The model accommodates a range of phenomena observed or inferred for alkaline/carbonatite complexes, including the following: 1, a growing calcite-dominated flotation assemblage with an apparently early magmatic mineralisation; 2, a residual liquid with high concentrations of incompatible metals; 3, variable carbonatite–pyroxenite–phoscorite rock relations; and 4, multiple phases of overprinting metasomatism.